Emissions and efficiencies of domestic appliances burning various fuels in South Africa - Graham, James Alexander Norman (Energy Research Centre, 2016)
Assessments of pollution from domestic fuel burning in South Africa have, in the main, based their conclusions on measured ambient pollutant concentrations. This approach does not allow for direct comparison of emissions from different domestic fuel burning appliances. Pollution from domestic fuel burning depends both on appliance efficiency, since a more efficient appliance· will burn less fuel, and appliance emission rates. A test cell was designed and built to measure efficiencies and emissions of various fuel/appliance combinations during cooking and space heating tests representative of field operating conditions. A range of fuels, liquid petroleum gas (LPG), paraffin, coal and wood were burnt in domestic appliances commonly used in South Africa. Emissions of gaseous pollutants, C02 , CO, NOx and HC, and particulate pollutants, total suspended particulates (TSP) and particles less than 2.Sμrn aerodynamic diameter, were measured.